Spontaneously Reduced Focal Atrial Tachycardia after Cannabis Overdose - Aicha, Boudar; Ahmed, Cheikh Bay; Mariem, Haboub; Rachida, Habbal (Journal of Cardiology and Cardiovascular Medicine, 2025)
Cardiac arrhythmias are frequent complications of the consumption of toxic substances, including cannabis, which can be fatal. We report in this case a patient who developed a cardiac arrhythmia-type focal atrial tachycardia a few moments after the consumption of an important dose of cannabis but which reduced spontaneously and without having administered any medication or an external electric shock. All the rest of the etiological assessment of this arrhythmia was negative and the arrhythmia was linked to the consumption of cannabis which is known to cause these complications.